2016
DOI: 10.1371/journal.pone.0155038
|View full text |Cite
|
Sign up to set email alerts
|

Genome-Scale Model Reveals Metabolic Basis of Biomass Partitioning in a Model Diatom

Abstract: Diatoms are eukaryotic microalgae that contain genes from various sources, including bacteria and the secondary endosymbiotic host. Due to this unique combination of genes, diatoms are taxonomically and functionally distinct from other algae and vascular plants and confer novel metabolic capabilities. Based on the genome annotation, we performed a genome-scale metabolic network reconstruction for the marine diatom Phaeodactylum tricornutum. Due to their endosymbiotic origin, diatoms possess a complex chloropla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
120
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 102 publications
(136 citation statements)
references
References 85 publications
6
120
0
Order By: Relevance
“…However, little is known regarding the specific role of the OUC across diverse physiological states. Recent work by Levering et al [120] identified the existence of a chloroplast ornithine cycle, the function of which was hypothesized to exchange NAD(P)H and ATP between the chloroplast and mitochondria. To gain insight into the biological role of these pathways and potential interactions between them, the diel and Fe-specific expression of genes and key metabolites involved in the OUC cycle were analyzed.…”
Section: Resultsmentioning
confidence: 99%
“…However, little is known regarding the specific role of the OUC across diverse physiological states. Recent work by Levering et al [120] identified the existence of a chloroplast ornithine cycle, the function of which was hypothesized to exchange NAD(P)H and ATP between the chloroplast and mitochondria. To gain insight into the biological role of these pathways and potential interactions between them, the diel and Fe-specific expression of genes and key metabolites involved in the OUC cycle were analyzed.…”
Section: Resultsmentioning
confidence: 99%
“…In 10 rescued NR knockouts, YFP expression was also induced when the cells were switched from NH 4 + to NO 3 2 media (Supplemental Figure 3). FTIR spectroscopy, previously calibrated using biochemical measurements (Levering et al, 2016;Mayers et al, 2013;Stehfest Figure 3A). During a 7-d time course experiment, three NR-KO lines (#9, 14, and 15) and the wild type were initially grown in NH 4 + media and then transferred into NO 3 2 -amended media and sampled periodically.…”
Section: Knocking Out Nitrate Reductase Transforms P Tricornutum Phymentioning
confidence: 99%
“…Indeed, expression profiles of genes encoding ACOAT, unCPS, GLDH, and ICDH (Supplemental Figures 5D to 5F and 11B) are more similar to the upstream NR cohort genes and support their substantive links to N-assimilation and C-metabolism. Plastidic ACOAT, a component of the recently proposed in silico ornithine-glutamine shuttle, transfers reducing equivalents generated by photosynthesis to the mitochondria (Levering et al, 2016). During N-stress, its secondary product, chloroplast-produced 2OG, may supplement the 2OG produced by ICDH in the mitochondria.…”
Section: The Loss Of Nr: the Scope Of Its Influencementioning
confidence: 99%
See 1 more Smart Citation
“…It streamlines the manual annotation and verification of metabolic pathways by providing a literature resource that is focused on biochemistry and physiology [19,20]. We created a bibliome of P. tricornutum-specific literature to facilitate a model that describes its metabolism [21]. The result is a comprehensive literature database enriched in biochemical, physiological, and molecular biology studies on P. tricornutum literature.…”
Section: Contents Lists Available At Sciencedirectmentioning
confidence: 99%